2011
DOI: 10.1007/s10592-011-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in westslope cutthroat trout Oncorhynchus clarkii lewisi: implications for conservation

Abstract: Twenty-five populations of westslope cutthroat trout from throughout their native range were genotyped at 20 microsatellite loci to describe the genetic structure of westslope cutthroat trout. The most genetic diversity (heterozygosity, allelic richness, and private alleles) existed in populations from the Snake River drainage, while populations from the Missouri River drainage had the least. Neighbor-joining trees grouped populations according to major river drainages. A great amount of genetic differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…The present study reveals the similar genetic pattern in terms of average heterozygosity levels as investigations done by Drinan, et al, (2011) using 20 microsatellites for determining the patterns of population genetic variation in westlope cutthroat trout, Oncorhynchus clarkia lewisii, in 25 populations from four rivers revealing a high level of average genetic diversity in the populations. These results can also be confirmed by the observations made by Coimbra et al, in 2017, where microsatellite markers were used for assessment of genetic diversity in four indigenous Sao Francisco River populations of Prochilodus argenteus and found that average observed heterozygosity was higher than the average expected heterozygosity in all the populations and genetic structure analysis revealed that all the four populations shared similar genetic patterns.…”
Section: Microsatellite Based Genetic Variations Between the Populationssupporting
confidence: 82%
“…The present study reveals the similar genetic pattern in terms of average heterozygosity levels as investigations done by Drinan, et al, (2011) using 20 microsatellites for determining the patterns of population genetic variation in westlope cutthroat trout, Oncorhynchus clarkia lewisii, in 25 populations from four rivers revealing a high level of average genetic diversity in the populations. These results can also be confirmed by the observations made by Coimbra et al, in 2017, where microsatellite markers were used for assessment of genetic diversity in four indigenous Sao Francisco River populations of Prochilodus argenteus and found that average observed heterozygosity was higher than the average expected heterozygosity in all the populations and genetic structure analysis revealed that all the four populations shared similar genetic patterns.…”
Section: Microsatellite Based Genetic Variations Between the Populationssupporting
confidence: 82%
“…Previous studies using microsatellite loci have shown marked genetic distinctions among westslope cutthroat trout populations (Young et al. 2004; Drinan et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed these expectations. Microsatellites and mtDNA revealed lower levels of genetic variation within the AB population compared to other sampled populations, a characteristic of a (i) recent founder event (e.g., Drinan et al 2011;Shikano et al 2010;reviewed by Dlugosch and Parker 2008), (ii) a genetic bottleneck (e.g., Leberg 1992;Menotti-Raymond and O'Brien 1993), or (iii) a recurrent founder population at the fringe of its range (e.g., Dennenmoser et al 2013;reviewed by Eckert et al 2008). Because the Alberta population is disconnected from the rest of the species' range, (iii) can be ruled out, leaving two alternative explanations.…”
Section: Genetic Diversitymentioning
confidence: 94%